Advanced therapeutic endoscopist and inflammatory bowel disease: Dawn of a new role - Modha, Kunjam (Baishideng Publishing Group Co., Limited, 2014)
Endoscopy plays a key role in the diagnosis and treatment of patients with inflammatory bowel disease (IBD). Colonoscopy has been traditionally used in the diagnosis of IBD and helps in determination of an important end point in patient management, “mucosal healing”. However, the involvement of an advanced endoscopist has expanded with innovations in therapeutic and newer imaging techniques. Endoscopists are increasingly being involved in the management of anastomotic and small bowel strictures in these patients. The advent of balloon enteroscopy has helped us access areas not deemed possible in the past for dilations. An advanced endoscopist also plays an integral part in managing ileal pouch-anal anastomosis complications including management of pouch strictures and sinuses. The use of rectal endoscopic ultrasound has been expanded for imaging of perianal fistulae in patients with Crohn’s disease and appears much more sensitive than magnetic resonance imaging and exam under anesthesia. Advanced endoscopists also play an integral part in detection of dysplasia by employing advanced imaging techniques. In fact the paradigm for neoplasia surveillance in IBD is rapidly evolving with advancements in endoscopic imaging technology with pancolonic chromoendoscopy becoming the main imaging modality for neoplasia surveillance in IBD patients in most institutions. Advanced endoscopists are also called upon to diagnose primary sclerosing cholangitis (PSC) and also offer options for endoscopic management of strictures through endoscopic retrograde cholangiopancreatography (ERCP). In addition, PSC patients are at increased risk of developing cholangiocarcinoma with a 20% lifetime risk. Brush cytology obtained during ERCP and use of fluorescence in situ hybridization which assesses the presence of chromosomal aneuploidy (abnormality in chromosome number) are established initial diagnostic techniques in the investigation of patients with biliary strictures. Thus advanced endoscopists play an integral part in the management of IBD patients and our article aims to summarize the current evidence which supports this role and calls for developing and training a new breed of interventionalists who specialize in the management of IBD patients and complications specific to those patients.